2024
DOI: 10.1051/0004-6361/202347230
|View full text |Cite
|
Sign up to set email alerts
|

JADES: The incidence rate and properties of galactic outflows in low-mass galaxies across 3 < z < 9

Stefano Carniani,
Giacomo Venturi,
Eleonora Parlanti
et al.

Abstract: We investigate the incidence and properties of ionised gas outflows in a sample of 52 galaxies with stellar masses between $10^7$ M$_ odot $ and $10^9$ M$_ odot $ observed with ultra-deep JWST/NIRSpec MSA spectroscopy as part of the JWST Advanced Deep Extragalactic Survey (JADES). The high-spectral resolution (R2700) NIRSpec observations allowed us to identify for the first time the potential signature of outflows in the rest-frame optical nebular lines in low-mass galaxies at $z>4$. The incidence fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Details of the data acquisition and reduction details are given in other works (Curtis-Lake et al 2023;Carniani et al 2024), which we summarise here. Targets were observed with three shutters in a three-point nod.…”
Section: Observation Overviewmentioning
confidence: 99%
“…Details of the data acquisition and reduction details are given in other works (Curtis-Lake et al 2023;Carniani et al 2024), which we summarise here. Targets were observed with three shutters in a three-point nod.…”
Section: Observation Overviewmentioning
confidence: 99%
“…, indicating that the ongoing outflow wind is unlikely to escape from the DM halos. We compare our results with Carniani et al (2024), who also identified [O III] outflows in z ∼ 4-7 galaxies from JADES spectroscopic data. We adopt the emission line measurements and M * estimation from Tables 2 and 3…”
Section: Broad [O Iii] Emission In Nirspec Spectroscopymentioning
confidence: 65%
“…The first possibility is different viewing angles of galaxies with biconical outflows, which has been observed in local galaxies (e.g., Venturi et al 2018) and recently proposed by Carniani et al (2024) at high z. Assuming a biconical outflow with an opening angle (θ), the broad emission lines can only be observed in the directions of the outflow.…”
Section: Origins Of [O Iii] Spatial Extent and Ongoing Outflowmentioning
confidence: 96%